2017
DOI: 10.1186/s12913-017-2488-5
|View full text |Cite
|
Sign up to set email alerts
|

Improving Emergency Department radiology transportation time: a successful implementation of lean methodology

Abstract: BackgroundEmergency Department overcrowding has become a global problem and a growing safety and quality concern. Radiology and laboratory turnaround time, ED boarding and increased ED visits are some of the factors that contribute to ED overcrowding. Lean methods have been used in the ED to address multiple flow challenges from improving door-to-doctor time to reducing length of stay. The objective of this study is to determine the effectiveness of using Lean management methods on improving Emergency Departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 23 publications
1
27
0
7
Order By: Relevance
“…This finding led to the organisation of a 5-day Lean project within the radiology department, focusing on improved turnaround time for radiography. Alike shown in other studies [18, 20], the Lean methodology was effective in reducing turnaround times for radiology results. Unfortunately, this reduction in waiting time for radiology results is only partially translated into reduced overall LOS.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This finding led to the organisation of a 5-day Lean project within the radiology department, focusing on improved turnaround time for radiography. Alike shown in other studies [18, 20], the Lean methodology was effective in reducing turnaround times for radiology results. Unfortunately, this reduction in waiting time for radiology results is only partially translated into reduced overall LOS.…”
Section: Discussionsupporting
confidence: 75%
“…Unfortunately, this reduction in waiting time for radiology results is only partially translated into reduced overall LOS. This is not surprising, since LOS is affected by factors beyond the ED process [20].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with other research. 115 Studies also reported other frequent tools used such as standard work (which is considered one prerequisite for flow); 93 the 5 steps of sort, set in order, shine, standardize, and sustain (the 5S, which are used to eliminate clutter and organize workstations); 33 and Kaizen (which is used for intensive team-based improvement projects 95 and for the engagement of key stakeholders 12 ). Such findings are consistent with those reported in other studies 19,44 and support the claim that most LH applications focus more on assessment and improvement tools and less on process-monitoring tools after LH interventions.…”
Section: Discussionmentioning
confidence: 99%
“…8 Hospitals provide many types of services in their outpatient departments, including emergency and clinic visits, imaging and other diagnostic services, laboratory tests, and ambulatory surgery. 9 Common indicators of patient flow in ambulatory care include patient waiting time 10,11 and length of stay (LOS) 12,13 ; however, time frames for patient throughput, and metrics used to monitor throughput, vary widely in both literature and practice. 14 Since the 1990s, in an effort to deal with both quality and cost issues, healthcare providers have looked outside the healthcare sector for inspiration and guidance.…”
Section: Introductionmentioning
confidence: 99%
“…ETT position is typically assessed using a frontal chest radiograph. However, due to high clinical volume, the delay in average turnaround time (TAT) for emergent chest radiographs is approximately 22.89 min [5]. Thus, an objective and accurate tool for characterization of ETT location on chest radiographs would be an invaluable asset in the acute care setting.…”
Section: Introductionmentioning
confidence: 99%